Black Panther: A Characterization Study of Erik Killmonger’s Machiavellianism - Aldila Tania Agatha; Ni Luh Nyoman Seri Malini; I Gusti Agung Istri Aryani (Soegijapranata Catholic University, 2020)
The study discusses and analyzes the characterization of a secondary character in the movie Black Panther, Erik Killmonger whose status as a villain described as a Machiavellian; a person known to be gruesome and unreliable to acquire everything he desires by any means necessary. The study functions as a source of knowledge for everyone who wishes to comprehend the deeper issue of a secondary character existence in a movie who does not get enough recognition, unlike the main character. This study used collecting and observing methods to acquire the data, Black Panther movie along with the movie script. A Qualitative research method is used to answer the problems of the study. It examined Killmonger’s characterization by using three theories; tridimensional aspects, Black Nationalism, and Machiavellianism. Discussion of Black History counts as a great necessity to give a clearer sense of the character’s background who described as an African-American male. Lastly, a descriptive method to analyze the problems and present the analysis is chosen to complete this study. The results of this study found innovative discussions on a Machiavellian character on the parameters of self-determination, nationalism, and racial prejudice. Killmonger’s Machiavellian character is categorized to have “cold” emotionality, lack of empathy, and manipulative. The study results also delivered fundamental truths about the current political and cultural situation in the United States, in which people still seek persistence in their everyday lives based on racial boundaries reflected by Killmonger’s mission as an African-American.